2009
DOI: 10.1021/la901919z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Density Functional Theory Study of the Tribochemical Wear Behavior of SiO2 in Humid and Alcohol Vapor Environments

Abstract: This paper investigates the reaction steps involved in tribochemical wear of SiO(2) surfaces in humid ambient conditions and the mechanism of wear prevention due to alcohol adsorption. The friction and wear behaviors of SiO(2) were tested in three distinct gaseous environments at room temperature: dry argon, argon with 50% relative humidity (RH), and argon with n-pentanol vapor pressure 50% relative to the saturation pressure (P/P(sat)). Adsorbed gas molecules have significant chemical influences on the wear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(147 citation statements)
references
References 47 publications
9
138
0
Order By: Relevance
“…Unlike water vapor, adsorbed alcohol vapor was found to reduce wear [124, 126−128]. Density functional theory calculations showed that the difference between water and pentanol vapor effects on silica glass wear might be related to how easily the Si−O−Si bond is cleaved upon impingement of these molecules from the gas phase [128]. The alkoxide termination of SiO 2 surface increased the energy barrier required to cleave the Si−O−Si bond compared to hydroxyl termination [128].…”
Section: Environmental Effect On Friction and Wear Of Oxides And Glassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike water vapor, adsorbed alcohol vapor was found to reduce wear [124, 126−128]. Density functional theory calculations showed that the difference between water and pentanol vapor effects on silica glass wear might be related to how easily the Si−O−Si bond is cleaved upon impingement of these molecules from the gas phase [128]. The alkoxide termination of SiO 2 surface increased the energy barrier required to cleave the Si−O−Si bond compared to hydroxyl termination [128].…”
Section: Environmental Effect On Friction and Wear Of Oxides And Glassesmentioning
confidence: 99%
“…Density functional theory calculations showed that the difference between water and pentanol vapor effects on silica glass wear might be related to how easily the Si−O−Si bond is cleaved upon impingement of these molecules from the gas phase [128]. The alkoxide termination of SiO 2 surface increased the energy barrier required to cleave the Si−O−Si bond compared to hydroxyl termination [128]. Further, it was found that the activation energy Crystalline oxide ceramics, such as Al 2 O 3 and ZrO 2 , share many aspects of the chemical properties of amorphous glasses when exposed to environmental water.…”
Section: Environmental Effect On Friction and Wear Of Oxides And Glassesmentioning
confidence: 99%
“…These results also suggest that the native oxide layer is removed during the running-in process of the Si-SiO x /SiO 2 pair. Such a running-in process has also been observed on macroscale silicon surfaces and DLC coating surfaces, where a sharp drop in friction force was attributed to the wear or removal of the surface oxide layer [10,29]. Figure 9 compares the adhesion and friction forces before and after 2000 cycles of sliding for the Si-SiO x /SiO 2 and Si-H/SiO 2 pairs.…”
Section: Friction-induced Reduction Of Adhesion During the Running-inmentioning
confidence: 59%
“…During running-in, because the peaks of asperities on rough contact surfaces are removed by mechanical interactions and valleys are filled by wear debris, the average surface roughness of specimens would decrease to a stable state [7,8]. The generation of wear debris as a three-body layer might lubricate contact interfaces [9,10]. As a result, both the friction force and the wear rate may decrease and then level off during macroscale running-in.…”
Section: Introductionmentioning
confidence: 99%
“…According to the corrosive wear model, h 0 _water is larger than h 0 _ethanol, resulting in an earlier arrival at the failure criterion. Since tribochemistry is a complicated process with multiple steps, such a single-step analysis [30] may not give a correct estimate of E a in Eq. (8).…”
Section: Discussionmentioning
confidence: 99%